2002
DOI: 10.1177/1069072702238402
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Examination of an Online Version of the Self-Directed Search

Abstract: The study examined the quality and utility of online administration of the Self-Directed Search (SDS) to high school students in a career exploration workshop. An Internet-based SDS version was designed; it included automatic scoring and immediate feedback to test takers, providing a three-letter occupational code along with verbal explanation of the results. SDS was taken by participants in their homes or in school ( n = 77), and compared to traditional administration of the SDS ( n = 73), either self-scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…At least one study (Barak & Cohen, 2002) has shown some evidence that individuals were more likely to indicate higher interest and confidence in the vocational domains of realistic, social, and enterprising when administered online versus paper and pencil. It was also recognized that a majority of the BIS/BAS Scale items were coded in the same direction, which may have created a responses bias towards the items.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…At least one study (Barak & Cohen, 2002) has shown some evidence that individuals were more likely to indicate higher interest and confidence in the vocational domains of realistic, social, and enterprising when administered online versus paper and pencil. It was also recognized that a majority of the BIS/BAS Scale items were coded in the same direction, which may have created a responses bias towards the items.…”
Section: Limitations Of Studymentioning
confidence: 99%
“…Future studies should also investigate other measurable criteria such as educational and career goals and aspirations. Other examples of career studies on Internet assessment exist (Barak & Cohen, 2002;Harris-Bowlsbey & Sampson, 2005;Oliver & Zack, 1999;Sampson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To date, very few researchers have investigated cross-mode equivalence using a repeated measures framework. Barak and Cohen (2002), investigating measurement equivalence of a popular measure of career interests, found that while testretest correlations were relatively high over a six-week period, three of the six subscale means were elevated for the Internet condition. As this study illustrates, the fundamental advantage of the repeated measures design over a between subjects design is the reduction in error variance associated with individual differences (Robinson, 1981).…”
Section: Demographics and Job Satisfactionmentioning
confidence: 99%